How does authentic leadership promote taking charge: The mediating effect of team social capital and the moderating effect of absorptive capacity - Chen, Guoqing; Wang, Jianjian; Dong, Zhiyuan; Zhang, Xiongtao (Frontiers in Psychology, 2023)
Authentic leaders are consistent with the expectations of Chinese traditional cultural values for leaders. The purpose of this study is to take team internal social capital (TISC) as the mediating variable and individual absorptive capacity as the moderating variable to explore the relationship between authentic leadership and taking charge. We collected 337 questionnaires from China and used linear regression to explore the influencing mechanisms and boundary conditions. The study results showed that the trickle-down of authentic leadership and the trickle-round of TISC can directly promote employees’ taking charge. Further, individual absorptive capacity positively moderated the relationship between TISC and taking charge. Our study provides a new perspective of leadership support for employees to implement taking charge in the context of high-power distance in China. From the perspective of authentic leadership, it is verified that leadership support is a necessary condition to motivate employees to implement proactive behavior. Moreover, compared with the research on the influence of leadership on proactive behavior, team-related and organization-related factors have not received enough attention. According to the social learning theory, we constructed an integrated framework for the first time in which leadership, team, and individual jointly affect taking charge.